[OP.7B.05] EFFECT OF ACUTE HYPERGLYCEMIA ON RENAL TISSUE OXYGENATION AS MEASURED WITH BOLD-MRI IN OVERWEIGHT INDIVIDUALS. (September 2016) - Vakilzadeh, N.; Milani, B.; Anex, C.; Stuber, M.; Zanchi, A.; Burnier, M.; Pruijm, M.
Abstract : Objective: Diabetic nephropathy affects 30% of diabetics, and its development has been linked to poor glycemic control. Animal studies have suggested that hyperglycemia induces transient renal hypoxia and thus kidney damage, yet this has not been previously tested in humans. In this interventional study we assessed whether hyperglycemia alters renal tissue oxygenation as measured with blood oxygenation level-dependent MRI (BOLD-MRI). Figure. No caption available. Design and method: Nineteen healthy overweight volunteers (age 37 ± 10 years, BMI 28.9 ± 3 kg/m 2, HbA1c 5.4 ± 0.3%, 57.9% women) were recruited and underwent an oral glucose tolerance test. Two had impaired glucose tolerance, none had diabetes. On a separate day, BOLD-IRM was performed under standard hydration conditions before, and after the intravenous administration of 0.15 g/kg of glucose in a 20% solution. R2* maps were analyzed using the concentric objects technique, a semi automatic procedure which divides the kidney parenchyma in twelve equal layers at increasing depth. R2* is a measure of local desoxyhemoglobin concentrations, with high R2* values corresponding to low oxygenation. Results: The mean glycemia rose from 4.5 ± 0.3 mmol/l to 9.0 ± 0.9, 8.9 ± 0.7, 7.7 ± 0.6 and 6.8 ± 0.8 mmol/l respectively 1, 10, 20 and 30 minutes after IV glucose administration, whereas circulating insulin levels increased, and no change occurred in HbA1c. The corresponding mean R2* values decreased significantly in all kidney layers (see figure), irrespective of glucose intolerance. In all layers, associations between R2* and insulin levels were stronger than between R2* and glycemia. Conclusions: These findings indicate that glycemia influences the R2* signal and should be measured before each BOLD-MRI. Hyperglycemia leads to an increase, not a decrease, of renal tissue oxygenation as measured with BOLD-MRI in healthy, obese volunteers. Whether this glucose-induced increase in oxygenation is due to alterations in renal perfusion, oxygen consumption or both, and whether this also occurs in patients with diabetes needs further study.